PENGARUH INTELLECTUAL CAPITAL TERHADAP PROFITABILITAS PERUSAHAAN (Studi Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2010-2012) - RISTRIANA MARGARET CANDRA RW; LELY KUMALAWATI (Jurnal Akuntansi dan Ekonomi Bisnis PSDKU kediri, 2014)
This study aimed to analyze that influence of intellectual capital on profitability. This study used several control variables that identified as factors that influence profitability, such as Value Added Human capital (VAHU), StructuralCapital Value Added (STVA), and Value Added Capital employed (VACA). The population used in this study was companies whose businesses are in manufacturing sectors. Sample was drawn by using purposive sampling method thus result 34 companies that will be used as samples for this study.The hypothesis in this study was tested by using multiple linear regression model. Simultaneous signification test (F test) and partial signification test (t test) with α = 5% are used to test hypothesis.